Mechanisms and implications of the gut microbial modulation of intestinal metabolic processes - Jyoti; Priyankar Dey (npj Metabolic Health and Disease)
Abstract Intestine-exclusive metabolic processes involve the degradation of dietary components and xenobiotics through intricate and dynamic interactions between the host epithelial cells and gut microbiota. Disruptions in this fragile equilibrium lead to metabolic and gastrointestinal diseases, highlighting the profound impact of the gut microbiota on the host intestinal metabolic processes. Gut microbes play a crucial role in influencing intestinal metabolic homeostasis by affecting nutrient sensing, gut hormones, neurotransmitters, and redox balance, collectively modulating mucosal gene expression and metabolic signaling pathways. These intestinal-level host-microbe metabolic interactions profoundly impact extra-intestinal tissues and organs. This comprehensive review provides mechanistic insights on the crucial role of gut microbiota in sustaining metabolic health by narrowing down to the gut-level metabolic interactions.